A rigless coiled tubing based Subsea Well Light Intervention System (SWIS) for enhanced oilfield recoveries - Costello, David J. (Curtin University, 2009)
The objectives of this thesis are to describe the Subsea Well Intervention System (SWIS) andto test the hypothesis that this system has significant potential economic benefits over asemi-submersible rig-based system which is normally used for completing common subseawell intervention procedures. These interventions are carried out in water depths from 200mto 3,000m.This thesis describes SWIS and its applications to subsea well interventions, discusses themain technical issues involved and provides an economic analysis of the cost benefit incomparison to semi-submersible and Drill Ship rig-based systems. Examples of subsea wellinterventions discussed in this thesis include: de-sanding, de-scaling, re-entry drilling andwellhead recovery. A discussion and analysis of the vessel response to the likely operatingsea states and an analysis of heave compensation for the Coiled Tubing (CT) system isincluded as these are critical factors to the technical viability of SWIS.SWIS is designed to have a light to medium level well intervention capability and it willprovide a tool for common subsea well intervention procedures. It is not designed for tubingchange out which is classified as a heavy level workover. In this case a conventional rig or aHydraulic Workover rig supported by a semi-submersible would be used.SWIS will be designed to include the following capabilities: Well and field abandonment;Artificial Lift Services; Re-entry Drilling using CT including well side tracking anddeepening operations (Operations to include CT under-balanced drilling and ThroughTubing); Deployment and recovery of Sand Control Screens using CT as a conveying tool;Through Tubing Completions using CT as a conveying tool; Post-completion well clean-upoperations; Slick-line and electric line operations and sub-sea wellhead maintenance andrecovery.The SWIS concept vessel is a large scale wave piercing catamaran which will be maintainedon station and heading into the prevailing sea using a Dynamic Positioning System (DPS).Initial modelling of the response of the vessel to typical expected operating sea stateconditions is encouraging because the results indicate that this type of vessel will provide astable platform from which to carry out typical subsea well intervention procedures.The modelling has demonstrated that the vessel motions (other than heave) are minimalunder the expected operating conditions and will be compensated by the Spooled CompositeRiser (SCR) and the CT.The heave amplitude and heave acceleration of the centre of gravity of the vessel will besuch that an off the shelf heave compensation system is available for the Spooled CompositeRiser (SCR). Research has indicated that existing CT heave compensation systems can bereadily modified for use with SWIS to provide the required level of motion compensation tocarry out intervention procedures in moderately rough seas.The hypothesis that a catamaran based platform used for the above purpose has significantpotential economic benefits over a semi-submersible for common types of interventionprocedures is supported by the research completed. It is concluded that the savings resultingfrom the use of the SWIS vessel compared to a semi-submersible would be around USD360,000 per day.It is also concluded from the research and modelling completed that SWIS is a technicallyand economically viable system. Based on the survey carried out it has the potential for ahigh degree of utilization in the East Asian and Australian offshore regions due of the abovecost saving. It also has the potential for a high degree of utilisation in other offshore regions such as Brazil and West Africa where sea states are light to moderate.